PENGEMBANGAN APLIKASI MOBILE UMKM UNTUK MENINGKATKAN PENJUALAN DAN JANGKAUAN PASAR - Sirait, Erwin; Purba, Arifin Tua (Jurnal Teknik Informasi dan Komputer (Tekinkom), 2024)
Micro, small, and medium enterprises (MSMEs) play a crucial role in the Indonesian economy, including in Pematangsiantar City, which has more than 29,000 MSMEs. However, MSMEs face various challenges, such as tight competition, limited market access, and lack of adoption of digital technology. This study aims to develop a mobile application for MSMEs to improve operational efficiency, expand market reach, and increase competitiveness. The methods used include literature studies, data collection from local MSMEs, flowchart and ERD-based system design, and application testing to ensure its functionality. The application developed has key features such as product management, digital transactions, and integration with logistics partners and payment systems. The results of the study show that digitalization through mobile applications can increase market reach, accelerate transactions, and provide convenience in business management for MSME actors. Thus, digital transformation through this application has the potential to be an effective solution in increasing MSME growth and supporting business sustainability in the digital era.